Serial Crowdfunding, Social Capital, and Project Success. (March 2017) - Butticè, Vincenzo; Colombo, Massimo G.; Wright, Mike
In this paper, we focus attention on serial crowdfunders, that is, entrepreneurs who repeatedly turn to crowdfunding to finance their projects. We argue that serial crowdfunders take advantage of the social contacts with those that backed their previous campaigns. This internal social capital developed within the platform, which is not available to "normal" serial entrepreneurs, makes serial crowdfunders' campaigns more successful than those launched by novice crowdfunders. However, this type of social capital is a substitute for the internal social capital built by backing other campaigns, and has a limited lifespan. Econometric results on a sample of 31, 389 Kickstarter campaigns confirm our contentions. Implications for research, practice, and policy are discussed.